Good Environment as Part of Human Right: A Case Study on Plastic Waste Post Pandemic - Puluhulawa, Fenty; Rusdiyanto Puluhulawa, Mohammad; Adelina Harun, Amanda (KnE Social Sciences, 2022)
The use of plastic waste causes various benefits in human life, but it also has negative impacts. Plastic waste has become part of environmental pollution and the Covid-19 pandemic has led to an increase in the use of plastic. The right to life is a part of human rights that every individual absolutely has. Human life depends on the surrounding environmental conditions, and the right to a good environment has a significant influence on the right to life. This study was based on the previous description, entitled “Good Environment as a Part of Human Rights (A Case Study on Plastic Waste)”. This study was a normative legal study, which used a conceptual and statute approach. This article discusses two main points namely: (1) The right to a good environment in the concept of human rights; (2) Environmental protection as part of the protection of human rights, with a case study on solid waste. The results showed that the right to a good, clean, and healthy environment is crucial in fulfilling the right to life. Without a good environment, the right to life could not be optimally enjoyed. Thus, protecting the environment from pollution, especially plastic waste, is part of the fulfillment of human rights. Keywords: environment, human right, plastic waste